Efecto de las nanopartículas de plata e hipoclorito de sodio al 5.25% en la inhibición del enterococcus faecalis en los canales radiculares mediante revisión narrativa (2021)
The success of a root canal consists of the elimination of the infected pulp tissue, the eradication of microorganisms such as Enterococus Faecalis that exist in the complex structure of the dental root canals, therefore preventing the recontamination of the pulp space after treatment to avoid a intraoperative or postoperative infection. An important step in reducing or eliminating root canal contamination is irrigation of the root canal with irrigating agents such as sodium hypochlorite and silver nanoparticles, which can penetrate mechanically inaccessible areas and have antimicrobial properties.